Radiation‐damage‐induced phasing: a case study using UV irradiation with light‐emitting diodes. Issue 3 (1st March 2016) - de Sanctis, Daniele; Zubieta, Chloe; Felisaz, Franck; Caserotto, Hugo; Nanao, Max H.
Abstract : A case study of radiation‐damage‐induced phasing is discussed using ultraviolet light‐emitting diodes to induce specific radiation damage. Abstract : Exposure to X‐rays, high‐intensity visible light or ultraviolet radiation results in alterations to protein structure such as the breakage of disulfide bonds, the loss of electron density at electron‐rich centres and the movement of side chains. These specific changes can be exploited in order to obtain phase information. Here, a case study using insulin to illustrate each step of the radiation‐damage‐induced phasing (RIP) method is presented. Unlike a traditional X‐ray‐induced damage step, specific damage is introduced via ultraviolet light‐emitting diodes (UV‐LEDs). In contrast to UV lasers, UV‐LEDs have the advantages of small size, low cost and relative ease of use.